TURONGGO YAKSO IN ETHNO-PHOTOGRAPHY - Perkasa, Mandira Citra; Prasetyo, Andry (Capture : Jurnal Seni Media Rekam, 2018)
The idea of a photographic creation entitled Turonggo Yakso in Ethnophotography is a follow-up in addressing the disappearance of the handwritten textbook of the founder of the art of Turonggo Yakso, which contains important notes on the art of Dongkol Village society. The book contains about the history of the art of Turonggo Yakso, the design of motion, and all the rules regarding the Baritan ceremony. The purpose of the creation of this work in an attempt to re-collect records in the form of text data from the interview results of the artists Turonggo Yakso, and visual data from the show performances which are packaged in ethnophotographic photos. The process of creating this work using the ethnophotographic method supported by Dipti Desai ie Pseudo-Ethnography or "Pseudo" ethnography, where the creator not follow the ethnographic methods strictly, but rely more on field data from interviews by informants and environmental observations. The creation of this work presents ethnophotographic works about the folk art of Turonggo Yakso in Dongko community, Trenggalek regency, East Java province from preparation, during the performance, to the end of the show.